ĐẶC ĐIỂM KHOÁNG VẬT - ĐỊA HÓA VÀ NGUỒN GỐC CÁC MỎ CHÌ - KẼM CẤU TRÚC LÔ GÂM, MIỀN BẮC VIỆT NAM - Anh, Trần Tuấn; I.V., GASKOV; Hòa, Trần Trọng; P.A., NEVOLKO; Dung, Phạm Thị; Niên, Bùi Ấn; Cẩn, Phạm Ngọc (Vietnam Journal of Earth Sciences, 2011)
Mineralogical and geochemical characteristics and forming conditions of lead - zinc deposits in Lo Gam structure, northern Vietnam In terms of reserves, lead - zinc deposits in the Lo Gam structure have made up more than 80% of the Pb-Zn resources in Vietnam. The deposits form four distinct ore zones are Lang Hich (Thai Nguyen), Cho Don, Cho Dien (Bac Kan), and Na Son (Ha Giang) relatively but basically belong to a common mineralization zone, extending over 100 km from east to west. The Pb-Zn deposits in the ore zone have similar characteristics to Mississippi type (MVT): distribution in Devonian carbonate sediments; concentrating at the intersection of differently orientated fractures; the mineral zone includes vein ore bodies and vascular network (bunch- and vein- disseminated types); presence of metasomatism (marmorization and developing of quartz - carbonate veins,..), low and moderate temperature hydrothermal (<250oC). However, different significances to MVT have also been recorded such as: widespreads of Permo-Triassic magmatisms; ore bedding is not typical; spectrum of the impurity elements are broad (In, Bi, Sb, Au, Ag, Cu, Cd) which is usually not specific to the MVT; sulfur isotopic composition value (δS34 = 2.68 ‰) close to the meteoritic sources; and ore impurities (In, Bi, Sb, Cu) show the endogenous and deep origin. These characteristics demonstrate the Pb-Zn deposits in carbonate and terrigenous sediments of Lo Gam structure belongs to the type of the low - average temperature hydrothermal, formed in association with Permo-Triassic magmatic activities. These differences in mineral composition, spectral of impurity elements as well as their concentration in different deposits show the complex processes of ore formation in association with different magma composition. Simple mineral composition and limited set of impurity elements (Cd, Ag, Sb, As) of the Lang Hich mine as well as the absence of magmatic activity makes it seems like MVT the most. In contrast, the Cho Don and Cho Dien Pb-Zn mining area characterize by enrichment in In (75.8 ppm), Sn (307.5 ppm), Cu (1080 ppm), Ag (157.7 ppm), Bi (99 ppm), As (13 650 ppm) show widespread magmatic activities (Phia Bioc granitoid complex, Cho Don syenite, ...). The presence of rare earth minerals (orthite) and high concentrations of Mo, Re and Rb in Na Son mine, probably related to the extensive development of the subalkaline volcanic and intrusive rocks (Tong Ba complex).